2020
DOI: 10.3389/fpsyt.2020.609120
|View full text |Cite
|
Sign up to set email alerts
|

Young Patients With Persistent and Complex Care Needs Require an Integrated Care Approach: Baseline Findings From the Multicenter Youth Flexible ACT Study

Abstract: Background: The Multicenter Youth Flexible ACT Study is an ongoing observational prospective cohort study that examines the effects of Youth Flexible ACT (Assertive Community Treatment) on young people with complex care needs who are difficult to engage in traditional (office-based) mental health services. However, a clear and detailed description of this patient group is lacking. In the current paper, we present baseline characteristics and psychosocial outcomes of the Youth Flexible ACT target group and expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…We selected the case of Michelle for description in the present article as it aptly demonstrates the need for integrated care across different domains, which is at the core of Youth Flexible ACT. Her age was above 18, she had problems in multiple life domains and she had a long history in care, all of which are hallmarks of the Youth Flexible ACT population ( 2 ). Yet, it should be noted that this case is not meant to serve as a representative client, because such a client does not exist due to the heterogeneous nature of the care models’ target population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We selected the case of Michelle for description in the present article as it aptly demonstrates the need for integrated care across different domains, which is at the core of Youth Flexible ACT. Her age was above 18, she had problems in multiple life domains and she had a long history in care, all of which are hallmarks of the Youth Flexible ACT population ( 2 ). Yet, it should be noted that this case is not meant to serve as a representative client, because such a client does not exist due to the heterogeneous nature of the care models’ target population.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it should be noted that this case is not meant to serve as a representative client, because such a client does not exist due to the heterogeneous nature of the care models’ target population. In fact, we previously showed that this population consists of four subgroups: the “internalizing,” “externalizing,” “non-specific,” and the “overly impulsive” subgroup ( 2 ). Michelle’s case best matches the “externalizing” subgroup, characterized by emotion regulation problems that manifest in disruptive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar fragmented mental health context in Norway, FACT-teams have shown to support closing of the gaps between organizations [ 28 ]. Additionally, the Dutch have included clients with a variety of diagnoses [ 29 ] and ages [ 30 ] that indicate a need for intensive treatment and not just adult clients with serious mental disorders.…”
Section: Introductionmentioning
confidence: 99%